Simulation of wake vortex effects for UAVs in close formation flight - Saban, Deborah; Whidborne, James F.; Cooke, Alastair K. (Royal Aeronautical Society, 2009)
This paper addresses the development of multiple UAV deployment simulation models that include representative aerodynamic cross-coupling effects. Applications may include simulations of autonomous aerial refuelling and formation flying scenarios. A novel wake vortex model was developed and successfully integrated within a Matlab/Simulink simulation environment. The wake vortex model is both sufficiently representative to support studies of aerodynamic interaction between multiple air vehicles, and straightforward enough to be used within real time or near real time air-to-air simulations. The integration process is described, and simulation results of a two vehicles formation flight are presented.
Keywords: large receiver aircraft aerodynamic interference directional stability dynamic stability air tanker